EFFECT OF ADDING YEAST (S. CEREVISIAE) TO THE DIET ON SOME PRODUCTION INDICATORS AND BLOOD BIOCHEMICAL PARAMETERS OF BROILERS - A. M. Mostafa; T. K. Dalla; F. A. Abdalaziz (مجلة الأنبار للعلوم الزراعية)
This study explored the effect of adding S. cerevisiae yeast to broiler diets on some of their production indicators and blood biochemical parameters. Ninety day-old chicks of broiler chickens (Ross-308) weighing 42 g on average were used in this study. The birds were randomly divided into three experimental groups of three replicates each (10 birds per replicate). The T1 group were fed a diet without any additives while the T2 and T3 groups received diets supplemented with 0.1% and 0.2% S. cerevisiae yeast, respectively. The T3 group performed the best with heavier body weights that increased at a rate of 4%. Its feed intake and feed conversion rates declined by 2% and 6%, respectively,  and no dead birds were recorded in the group at p ≤ 0.05. The results indicate that the concentrations of total protein, albumin, and globulin in blood serum increased by 13%, 17%, and 4%, respectively, while glucose and cholesterol levels decreased by 18% and 27%, respectively in the T3 group (p ≤ 0.05).